Shock Wave Analysis at Signalized Intersections (Case Study of Cikaret–Cibinong Intersection) - Rulhendri, Rulhendri; Nopianda, Riky Sanjaya; Alimuddin, Alimuddin (ASTONJADRO, 2026)
The signalized intersection of the Cikaret - Cibinong highway is one of the signalized intersections in the Cibinong sub-district, Bogor Regency with a road length of 2.4km causing a shock wave event on the road section due to changes in flow values ​​and density that often experience congestion during rush hour, for that a study was conducted to analyze the characteristics of shock waves at the highway intersection to determine the recovery of the queue length caused by increased traffic flow. This study was conducted for 3 days on Monday, Thursday and Sunday, in the morning (06.00 - 09.00), afternoon (10.00 - 12.00), evening (16.00 - 18.00). The characteristics of the shock waves that occur are current, forward formation, front stop, backward formation, forward recovery, backward recovery, moving forward in one direction, delay, maximum queue length, normalization time. Based on the research results, the results of the mathematical relationship calculation between volume, speed and density in the greenshields model to analyze the queue length value using the shock wave value obtained the maximum volume (VM) 521.2483smp/hour, the maximum density Dm of 28.707smp/km and taken the flow condition VA = 300.56smp/hour which experienced a delay of 116 seconds, the queue length (QM) was 244 meters and the normalization time of 189.550 seconds was higher than the duration of the green light which was 52 seconds. This means that when the light changes from green to red, not all vehicles queuing cross the stop line. According to the results of the processing and analysis, the results of the mathematical relationship between volume, speed and density were obtained from the determination coefficient value (R2) using the greenshields model, which is 0.1774.